Supportive Educative Interventions Based on The Information Motivation Behavioral Skills on the Compliance of Antiretroviral Therapy and Quality of Life in HIV Patients - Nursalam, Nursalam; Martawinarti, Rts Netisa; Wahyudi, Andri Setiya (International Journal of Psychosocial Rehabilitation, 2020)
Anthroviral therapy (ART) is the only drug to treat the HIV virus. Non-adherence to ART is a major factor in treatment failure and one of the causes of decreased quality of life in HIV patients. This Study aimed was to improve the compliance and quality of life in patients with HIV. A quantitative research with quasi-experimental design with 30 control samples and 30 intervention samples, the sampling technique used was purposive sampling, the dependent variable was adherence and quality of life. In this study using instruments in the form of a questionnaire consisting of 3 behavioral skills, compliance (MARS), and quality of life (WHOQOL). Analysis using Shapiro Wilk, paired T test and Wilcoxon sign rank test. Interventions are given 3 times a month. The results showed the effect of intervention on adherence seen from the p value of 0.014 (